2019
DOI: 10.1177/1010539519848275
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term and Long-Term Effects of a Combined Intervention of Rope Skipping and Nutrition Education for Overweight Children in Northeast China

Abstract: The aim of the present study was to evaluate whether an exercise intervention, nutrition education, or the combination of both were effective in weight reduction and maintenance for rural school children. Two hundred twenty-nine primary school children aged 9 to 12 years determined as overweight/obese were randomly assigned to 1 of 4 groups: exercise intervention, nutrition education, combination of both, and control. Nutrition education and rope-skipping sessions were performed for 2 months. Anthropometric me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 32 publications
2
33
0
2
Order By: Relevance
“…Although daily total energy intake was reduced in all groups after 6 months of intervention, changes in energy intake did not show a significant difference between the three groups. Similar to the results of our study, the previous studies which did not focus on calorie restriction reported reduced energy intake after the lifestyle intervention [49,50]. Moreover, a previous meta-analysis reported that structured physical activity interventions were more likely to lead to decreased daily energy intake in adolescents with obesity [51].…”
Section: Plos Onesupporting
confidence: 91%
“…Although daily total energy intake was reduced in all groups after 6 months of intervention, changes in energy intake did not show a significant difference between the three groups. Similar to the results of our study, the previous studies which did not focus on calorie restriction reported reduced energy intake after the lifestyle intervention [49,50]. Moreover, a previous meta-analysis reported that structured physical activity interventions were more likely to lead to decreased daily energy intake in adolescents with obesity [51].…”
Section: Plos Onesupporting
confidence: 91%
“…These studies included 15 cluster randomized control trials (CRCTs), 10 quasi-experiments, and 3 randomized controlled trials (RCTs), which accounted for 53.6%, 35.7%, and 10.7%, respectively. They were conducted in nine countries and two territories from different regions of Asia, namely mainland China [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], Hong Kong–China [ 37 , 38 ], Taiwan–China [ 39 ], Korea [ 40 ], Turkey [ 41 , 42 , 43 ], Lebanon [ 44 , 45 ], Israel [ 46 , 47 ], Iran [ 48 ], India [ 49 ], Malaysia [ 50 ], and Thailand [ 51 ]. The majority of the studies (75%) took place in upper-middle income countries [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 41 , 42 , 43 , 44 , 45 , 46 , 49 , 51 , 52...…”
Section: Resultsmentioning
confidence: 99%
“…Practical examples, particularly cooking skills and food labels, are important elements in nutrition education to develop students' skill efficacy which will improve their dietary behaviors as a long-term effect (Anand et al, 2015;Hao et al, 2019;Savage et al, 2016;WHO Europe, 2006). The present study found cooking activities at the Boy/Girl Scout club a potential practical activity, although still limited to preparing simple dishes such as fried rice.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a deep understanding of enablers, barriers and motives of adolescents' food choices will be valuable to inform policymakers on effective interventions. Studies have investigated the role of SBNE to improve malnutrition among adolescents (Hao et al, 2019;Jarpe-Ratner et al, 2016;Kattelmann et al, 2019;Meiklejohn et al, 2016) and explored teachers' experiences with SBNE (Dudley et al, 2015;Jones and Zidenberg-Cherr, 2015;Jørgensen et al, 2014). Because the ultimate goal of SBNE is students' well-being, understanding students' needs for nutrition education may serve as a potential enabler to improve SBNE delivery.…”
Section: Introductionmentioning
confidence: 99%